2017
DOI: 10.4103/0366-6999.204936
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Dosimetric Study of Biliary Stent Loaded with Radioactive 125I Seeds

Abstract: Background:A novel radioactive 125I seed-loaded biliary stent has been used for patients with malignant biliary obstruction. However, the dosimetric characteristics of the stents remain unclear. Therefore, we aimed to describe the dosimetry of the stents of different lengths — with different number as well as activities of 125I seeds.Methods:The radiation dosimetry of three representative radioactive stent models was evaluated using a treatment planning system (TPS), thermoluminescent dosimeter (TLD) measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…Using the same setup of prescription points and the same ROI defined in Jung et al, 16 (ROI ref ), our study showed a larger decrease of the doses at the prescription points (17.8% vs. 10.8%-14.8%) and a larger deviation of the radial doses on the surface of ROI ref (10.8% vs. 4.3%). Compared with Yao et al, 19 the influence of the stent on the radial dose rate is much larger in our work (24.2% vs. 6.9%) for the 6-cm stents loaded with 16 125 I seeds. These differences are mainly caused by the different stent geometries adopted.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Using the same setup of prescription points and the same ROI defined in Jung et al, 16 (ROI ref ), our study showed a larger decrease of the doses at the prescription points (17.8% vs. 10.8%-14.8%) and a larger deviation of the radial doses on the surface of ROI ref (10.8% vs. 4.3%). Compared with Yao et al, 19 the influence of the stent on the radial dose rate is much larger in our work (24.2% vs. 6.9%) for the 6-cm stents loaded with 16 125 I seeds. These differences are mainly caused by the different stent geometries adopted.…”
Section: Discussioncontrasting
confidence: 84%
“…Yao et al evaluated the dosimetry of seed-loaded stent models of three configurations using Monte Carlo (MC) simulations, TG-43 methods implemented in a TPS, and thermoluminescent dosimeter (TLD) measurements, and their results suggested that the influence of the metal stent on the dose distribution was negligible. 19 Jung et al investigated the dose distributions surrounding 125 I seed-loaded stents with a diameter of 12 mm and a length of 60 mm by MC simulation and they found that the impact of metallic stent was significant. 16 Considering the disagreement in the conclusions of these previous studies, it was deemed necessary to further study the dose influence of stent, especially when the previous studies adopted simplified stent models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasingly detailed studies of intraluminal implantation of 125 I seed-loaded stents,[ 23 ] stenting of the portal vein combined with implantation of 125 I seed strands has become a new treatment of HCC with PVTT. In clinical application of this technology, most researchers have used the formula: obstruction length (mm)/4.5 + 4 to calculate the required number of 125 I seeds.…”
Section: Discussionmentioning
confidence: 99%
“…A suitable alternative is the use of 125 I radioactive seeds that can continuously release low-dose grays to inhibit cancer cells and promote apoptosis. Many animal and clinical studies have confirmed that 125 I brachytherapy can obviously increase the local control rate and improve long-term survival (10)(11)(12)(13). At present, the most commonly tools for the permanent implantation of radioactive 125 I seeds is CT or US guidance, which requires percutaneous trans-stomach puncture to the tumor located at the head of pancreas frequently, which is a high-risk treatment due to the complex surrounding vessels.…”
Section: Introductionmentioning
confidence: 99%